PENGARUH KONSERVATISME AKUNTANSI, UKURAN PERUSAHAAN, PERENCANAAN PAJAK, PROFITABILITAS, LEVERAGE, DAN CAPITAL INTENSITY TERHADAP PENGHINDARAN PAJAK - Khasanah, Febriana Iin Nur; Kusumadewi, Hermala (LPPM Universitas Bina Bangsa, 2025)
This study aims to determine the effect of accounting conservatism, firm size, tax planning, profitability, leverage, and capital intensity on tax avoidance. Tax avoidance in this study is measured using the Cash Effective Tax Rate (CETR). This type of research is quantitative with a causal approach. The population in this study consisty of all property and real estate sector listed in IDX periode 2019-2023. The sampling technique used purposive sampling method, the result of 85 samples from 17 companies. The result of this study indicate that firm size, profitability, and capital intensity an effect on tax avoidance. While, accounting conservatism, tax planning, and leverage do not affect tax avoidance.